The criterion mode of evaluating functioning of stomatologic polyclinic - Grynin, V M; Avetisyan, A Yu; Reshetnikov, V A (Problemy sotsial'noi gigieny, zdravookhraneniia i istorii meditsiny, 2022)
To improve quality and efficiency of primary health care and to strengthen its preventive directivity is possible through health care modernization including implementation of management technologies, development of database for evaluation and control. The purpose of the study is to develop method of evaluating activity of stomatologic clinic. The methodology was based on concepts of "functional systems" and "decision making". The listing of informative criteria was based on data analysis of functioning of stomatologic service of the Chechen Republic in 2002-2016 and results of sociological survey of stomatologists (n=181), health care administrators in stomatology (n=45), paramedics (n=220) and patients (n=359). The experts (n=13) developed required number of criteria and their gradation. The algorithm of evaluating activity of stomatologic clinic was developed using systematic approach. The listing of 52 criteria and their 10 blocks were established. The experts established coefficients of significance of criteria (0.0084-0.0781; ≥0.0224 - more significant, <0.0224 - less significant). Three levels were determined for each criterion (according principle of minimization) that became a basis for calculation of integrated indicator of efficiency of functioning of stomatologic polyclinic. The expanded methodological approaches ensure comparartivity of estimates of stomatologic polyclinic in various time periods. The health care authorities have opportunity to objectify analysis of functioning of a number of polyclinics in different periods.